If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(9x + -15) = 15(1 + 9x) Reorder the terms: -1(-15 + 9x) = 15(1 + 9x) (-15 * -1 + 9x * -1) = 15(1 + 9x) (15 + -9x) = 15(1 + 9x) 15 + -9x = (1 * 15 + 9x * 15) 15 + -9x = (15 + 135x) Add '-15' to each side of the equation. 15 + -15 + -9x = 15 + -15 + 135x Combine like terms: 15 + -15 = 0 0 + -9x = 15 + -15 + 135x -9x = 15 + -15 + 135x Combine like terms: 15 + -15 = 0 -9x = 0 + 135x -9x = 135x Solving -9x = 135x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-135x' to each side of the equation. -9x + -135x = 135x + -135x Combine like terms: -9x + -135x = -144x -144x = 135x + -135x Combine like terms: 135x + -135x = 0 -144x = 0 Divide each side by '-144'. x = 0 Simplifying x = 0
| 4+5=-55-6x | | x-9=-6x+19 | | 12x+7x=-5 | | -4(3-6D)=2(3d-8) | | 25a^2+2a=5868 | | 3x-10=-22+4x | | 2x+20=92 | | 13a+9b=13750 | | 9x=10+3x | | 13a+9b=13 | | x+3.1=1.6 | | x+.1=1.6 | | -x+3=-45+5x | | a^2+a=25 | | 7-2x=-4+23 | | y=100+75 | | 2a^2-16ab+14b^2=0 | | 40x+8(1.5)=525 | | (x-(2-5i))(x-(2+5i))=0 | | 4x-2-5x=-7 | | 81+256=625 | | 3-6x=3x-2x-46 | | 0.000579a^2-a+286.25=0 | | 6-5n=n+9 | | p+7=1.1 | | -7/8x-1/2=3/16x+5 | | 1x+2x+3x=82 | | 18+32=50 | | -(7x^3+2x^2-3)+(5x^2-30)= | | -6=2x-5x+3 | | 35x^2+21x= | | 5(6t-3)=6(3t-1) |